Effects of Deposition Time And PH on The Characterization of Chemically Synthesized Composite Nano-Wires of Cu2S Thin Films - Ahmed, Honar S.; Mohammed, Raghad Y.; Khalil, Mohammed Hussein (Science Journal of University of Zakho, 2021)
The chemical bath deposition technique (CBD) had used for depositing Cu2S thin films on the glass substrates. It found that thickness and deposition rate were significantly dependent on deposition parameters (deposition time and pH value). XRD data indicates that at different deposition times and pH values are given amorphous structure except for the deposited thin film of (8hours) and, pH of (10.4) the structure was crystalline. The morphology of the deposited thin films remarkably changed as the deposition time increased. Optical transmittance measurements illustrate that transmission of the thin films decreases from 93.27% for a deposition time of 4 hours to 81.73 for deposition time of 10 hours and, the maximum transmission rate of the films is 95.21 % with pH=8.4 and decreases to 28.39 % with pH=11.4. Also, optical studies revealed that Cu2S thin film with direct energy bandgap decreased from 3.04 to 2.78 eV as deposition time increased and from 3.09 to 2.32 eV as pH increased.